Partial Fraction `(x^5-2x^4+x^3+x+5)/(x^3-2x^2+x-2)`Solution:The numerator `x^5-2x^4+x^3+x+5` is of degree 5 and the denominator `x^3-2x^2+x-2` is of degree 3. So first do the long division
long division of `x^5-2x^4+x^3+x+5` and `x^3-2x^2+x-2`
Final Solution
| `` | `x^2` | | | | | | | | | | | | |
`color{blue}{x^3-2x^2+x-2}` | `` | `x^5` | `-` | `2x^4` | `+` | `x^3` | `+` | `0x^2` | `+` | `x` | `+` | `5` | | |
| `` | −`x^5` | `-` | +`2x^4` | `+` | −`x^3` | `-` | +`2x^2` | | | | | | `color{green}{x^2} xx (color{blue}{x^3-2x^2+x-2})` |
| | | | | | | `` | `2x^2` | `+` | `x` | `+` | `5` | | |
Final answer `= "Quotient" + (color{Magenta}{"Remainder"})/(color{blue}{"Divisor"})`.
`:.` Final answer = `x^2 + (color{Magenta}{2x^2+x+5})/(color{blue}{x^3-2x^2+x-2})`
Here, Divisor = `x^3-2x^2+x-2`
Dividend = `x^5-2x^4+x^3+x+5`
Quotient = `x^2`
Remainder = `2x^2+x+5`
Step by step division solution
Step - 1 : 1. Divide the first term of the dividend by the first term of the divisor : `(x^5)/(x^3)=color{green}{x^2}`
2. Write down the calculated result `color{green}{x^2}` in the upper part of the table.
3. Multiply it by the divisor `color{green}{x^2} xx (color{blue}{x^3-2x^2+x-2})=color{red}{x^5-2x^4+x^3-2x^2}`
4. Subtract this result from the dividend
`(x^5-2x^4+x^3+0x^2+x+5)-(color{red}{x^5-2x^4+x^3-2x^2})=color{Magenta}{2x^2+x+5}`
| `` | `x^2` | | | | | | | | | | | | |
`color{blue}{x^3-2x^2+x-2}` | `` | `x^5` | `-` | `2x^4` | `+` | `x^3` | `+` | `0x^2` | `+` | `x` | `+` | `5` | | |
| `` | −`x^5` | `-` | +`2x^4` | `+` | −`x^3` | `-` | +`2x^2` | | | | | | `color{green}{x^2} xx (color{blue}{x^3-2x^2+x-2})` |
| | | | | | | `` | `2x^2` | `+` | `x` | `+` | `5` | | |
The long division gives
`(x^5-2x^4+x^3+x+5)/(x^3-2x^2+x-2) = x^2 + (2x^2+x+5)/(x^3-2x^2+x-2)`
Now find partial fraction of `(2x^2+x+5)/(x^3-2x^2+x-2)`
1. Factors the denominator
`(2x^2+x+5)/(x^3-2x^2+x-2)=(2x^2+x+5)/((x-2)(x^2+1))`
2. Partial fraction for each factors
`:. (2x^2+x+5)/((x-2)(x^2+1))=A/(x-2)+(Bx+C)/(x^2+1)`
3. Multiply through by the common denominator of `(x-2)(x^2+1)`
`:. 2x^2+x+5=A xx (x^2+1)+(Bx+C) xx (x-2)`
`:. 2x^2+x+5=Ax^2+A+Bx^2-2Bx+Cx-2C`
4. Group the `x`-terms and the constant terms
`:. 2x^2+x+5=(A+B)x^2+(-2B+C)x+(A-2C)`
5. Coefficients of the two polynomials must be equal, so we get equations
`A+B=2`
`-2B+C=1`
`A-2C=5`
Solution of equations using Elimination method
Total Equations are `3`
`a+b+0c=2 -> (1)`
`0a-2b+c=1 -> (2)`
`a+0b-2c=5 -> (3)`
Select the equations `(1)` and `(3)`, and eliminate the variable `a`.
`a+b=2` | ` xx 1->` | | `` | `a` | `+` | `b` | | | `=` | `2` | `` |
| | − | |
`a-2c=5` | ` xx 1->` | | `` | `a` | | | `-` | `2c` | `=` | `5` | `` |
| | |
|
| | | | | `` | `b` | `+` | `2c` | `=` | `-3` | ` -> (4)` |
Select the equations `(2)` and `(4)`, and eliminate the variable `b`.
`-2b+c=1` | ` xx -1->` | | | | `` | `2b` | `-` | `c` | `=` | `-1` | `` |
| | − | |
`b+2c=-3` | ` xx 2->` | | | | `` | `2b` | `+` | `4c` | `=` | `-6` | `` |
| | |
|
| | | | | | | `-` | `5c` | `=` | `5` | ` -> (5)` |
Now use back substitution method
From (5)
`-5c=5`
`=>c=(5)/(-5)=-1`
From (2)
`-2b+c=1`
`=>-2b+(-1)=1`
`=>-2b-1=1`
`=>-2b=1+1=2`
`=>b=(2)/(-2)=-1`
From (1)
`a+b=2`
`=>a+(-1)=2`
`=>a-1=2`
`=>a=2+1=3`
Solution using back substitution method.
`a=3,b=-1,c=-1`
After solving these equations, we get
`a=3,b=-1,c=-1`
Substitute these values in the original fraction
`((x^5-2x^4+x^3+x+5))/((x-2)(x^2+1))=x^2+(3)/(x-2)+(-1x-1)/(x^2+1)`
This material is intended as a summary. Use your textbook for detail explanation.
Any bug, improvement, feedback then